PTH-059 Cost reductions and in- patient bed days saved by an inflammatory bowel disease nurse helpline. (17th June 2017) - Kemp, K; Brooks, J; Kirkbride, M; Birchall, F; Dutton, H; Levison, S
Abstract : Introduction: Reducing emergency admissions is a recognised Quality Premium outcome by the Better Care Fund (NHS England) and it is one the of outcome measures against which CCGs are required to set targets. The IBD helpline can be directly translated into in-patient beds saved and direct costs. This prospective audit measured both cost savings and income generated and also calculated A and E avoidances and in-patient beds saved. Method: The aim was to measure how an IBD Nurse helpline could influence key outcomes. Between 1/1/2016-30/6/2016 all calls to the IBD helpline were prospectively audited in a large tertiary Hospital Trust. Patients were also asked what action they would take if there were no helpline available at that time point and their thoughts/concerns recorded. The tariff from the helpline, the OPDs saved, number of in- patient bed days saved and costs were calculated with the Specialist Medicine Informatics and Accountants. Results: In 6 mths there were 876 IBD related appropriate and chargeable calls to the helpline. This tariff generated an income of £26 280. 741 OPD s were avoided resulting in £62 244 savings to the CCG. 76 A and E attendances were directly avoided. Based on a 5 day in-patient stay (average in-pt stay for previous 6 mths) 380 days were saved over 6mth, saving 2.1 beds per day. The 2.1 bed days per day saved equates to £96 000 over the 6mth period. Of the 90 'other', 32 were given OPDs generating an income £3648. 6 patients were admitted directly from the helpline. 273 GP consultations were avoided. Conclusion: IBD helplines are a vital resource for IBD patients. There is great emphasis demonstrating the value of the IBD nurse in both monetary terms and patient experience. The presence of an IBD helpline can assist NHS Trusts and CCGs to meet national targets by avoiding A and E admissions and in-patient bed stays, reducing opds whilst maintaining a high quality, efficient and optimal service. Disclosure of Interest: K. Kemp Conflict with: Abbvie, MSD, Takeda, Janssen, J Brooks: None Declared, M Kirkbride: None Declared, F Birchall: None Declared, H Dutton: None Declared, S Levison: None Declared